Clinical aspects of patients with sarcoglycanopathies under steroids therapy - Marco A. V. Albuquerque; Osório Abath-Neto; Jéssica R. Maximino; Gerson Chadi; Edmar Zanoteli; Umbertina C. Reed (Arquivos de Neuro-Psiquiatria)
Patients with sarcoglycanopathies, which comprise four subtypes of autosomal recessive limb-girdle muscular dystrophies, usually present with progressive weakness leading to early loss of ambulation and premature death, and no effective treatment is currently available. Objective To present clinical aspects and outcomes of six children with sarcoglycanopathies treated with steroids for at least one year. Method Patient files were retrospectively analyzed for steroid use. Results Stabilization of muscle strength was noted in one patient, a slight improvement in two, and a slight worsening in three. In addition, variable responses of forced vital capacity and cardiac function were observed. Conclusions No overt clinical improvement was observed in patients with sarcoglycanopathies under steroid therapy. Prospective controlled studies including a larger number of patients are necessary to determine the effects of steroids for sarcoglycanopathies.